PENINGKATAN PEMAHAMAN MAHASISWA PROGRAM STUDI HUBUNGAN MASYARAKAT MELALUI WEBINAR PUBLIC RELATIONS - Widya Novchi, Raja; Hanafi, Khusnul; Jayus, Jayus; Putra, Eka (COVIT (Community Service of Tambusai), 2022)
The increasing cases of Covid-19 have an impact on every aspect including in terms of the economy, health and other sectors including the organization's Corporate Social Responsibility (CSR) program. The problem that arises is how public relations or public relations is able to carry out CSR in the midst of a pandemic so that people are able to feel the positive benefits of the organization's presence. The PKM activity started with the initiation of the head of the service who in charge of Crisis Issue Management and Corporate Social Responsibility (CSR) courses. The goal is to carry out the tri dharma of higher education in the fields of teaching and service. With this PKM, students not only get theory in lectures but can also interact with PR practitioners, increase their knowledge of PR and get direct experience of public relations work in the field. PKM activities were carried out online through the zoom meeting application on Sunday, December 19, 2021, attended by 130 participants. The implementation method is in the form of lectures and discussions with two resource persons from The National University of Malaysia and PR practitioner PT. Riau Pulp and Paper. The results of the PKM activity showed that participants were able to interact with the presenters, gain direct knowledge and experience about PR work, participants asked questions, discussed and answered quizzes given by the two resource persons. The output of service activities is the publication of two news articles in online mass media, namely bingkairiau.com and riaumag.com Keywords: CSR, Public Relations